2014
DOI: 10.1095/biolreprod.114.121723
|View full text |Cite
|
Sign up to set email alerts
|

Use of the CRISPR/Cas9 System to Produce Genetically Engineered Pigs from In Vitro-Derived Oocytes and Embryos1

Abstract: Targeted modification of the pig genome can be challenging. Recent applications of the CRISPR/Cas9 system hold promise for improving the efficacy of genome editing. When a designed CRISPR/Cas9 system targeting CD163 or CD1D was introduced into somatic cells, it was highly efficient in inducing mutations. When these mutated cells were used with somatic cell nuclear transfer, offspring with these modifications were created. When the CRISPR/Cas9 system was delivered into in vitro produced presumptive porcine zygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
265
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(281 citation statements)
references
References 40 publications
5
265
0
4
Order By: Relevance
“…Moreover, after the generation of the first transgenic piglet by sperm injection, ICSI gained importance as a new tool for inducing genetic modifications in farm animals (Kurome et al 2006, Garcia-Vazquez et al 2010. However, the advent of CRISPR-Cas9 system for genetic engineering lead to the replacement of ICSI by regular or IVF zygotes for the generation of genetically modified animals (Hai et al 2014, Whitworth et al 2014, Proudfoot et al 2015, Wang et al 2015, Bevacqua et al 2016.…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after the generation of the first transgenic piglet by sperm injection, ICSI gained importance as a new tool for inducing genetic modifications in farm animals (Kurome et al 2006, Garcia-Vazquez et al 2010. However, the advent of CRISPR-Cas9 system for genetic engineering lead to the replacement of ICSI by regular or IVF zygotes for the generation of genetically modified animals (Hai et al 2014, Whitworth et al 2014, Proudfoot et al 2015, Wang et al 2015, Bevacqua et al 2016.…”
Section: General Overviewmentioning
confidence: 99%
“…In conclusion, ICSI-MGT in farm animal has only produced repeatable results in pigs, wherein several transgenic offspring have resulted. However, interest in producing transgenic animals by ICSI-MGT has decreased with the advent of new tools of gene edition (CRISPR-Cas9 and TALEN system), which are technically simpler (Hai et al 2014, Whitworth et al 2014, Proudfoot et al 2015, Wang et al 2015, Bevacqua et al 2016). …”
Section: Icsi-mediated Gene Transfer (Icsi-mgt)mentioning
confidence: 99%
“…However, gene targeting has limited applications in some organisms due to time-consuming procedures and the lack of available embryonic stem cells. Many recent studies have shown that CRISPRCas9 technology could be used for rapidly generating targeted genome modifications in the germ lines of various model organisms [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , which will significantly advance the functional genomics. Microinjection of Cas9-encoding mRNA and customizable sgRNA into one-cell stage zebrafish embryos is able to efficiently modify the target genes in vivo in a simple, rapid and scalable manner 13,14 .…”
Section: Applications Of Crispr/cas9 Technology: Crispr-cas9 In the Gmentioning
confidence: 99%
“…Enfin, il a été possible de muter le génome de Plasmodium Yolii, le parasite responsable de la malaria dans un modèle murin [33]. Des modèles de maladies héréditaires humaines ont également été créés chez le porc [34] et le singe [35] grâce à la technologie CRISPR/Cas9.…”
Section: Coupures Hors Cibleunclassified